Ageism in healthcare and social care settings in Europe: a scoping review - Poli, Stefano; Giannoni, Paola; Moretti, Giada (SocietàMutamentoPolitica, 2026)
Ageism is a widespread, complex form of discrimination negatively affecting older adults’ health, well-being, and access to healthcare and social services. In rapidly ageing societies, particularly in Europe, it has become a critical social determinant of health, shaping clinical decision-making, professional practices, organizational routines and health policies. Despite growing research on ageism, evidence remains fragmented, highlighting the need for systematic synthesis. This scoping review maps recent literature on ageism toward older adults in healthcare and social care settings. Searches were conducted in Scopus and PubMed for peer-reviewed articles published between 2021 and 2025, following the COVID-19 emergency. Fifty-five studies in European contexts were included and analysed using Template Analysis with MAXQDA. Findings show that ageism operates across four interrelated levels: internalized/self-ageism, individual/interpersonal, institutional/organizational, and structural/systemic. These levels are associated with a range of specific outcomes: internalized stereotypes, psychological distress, compromised clinical communication, ethical implications, biased service design, health and digital inequalities. While educational and organizational efforts are effective, they remain insufficient. Addressing ageism requires integrated, multilevel strategies, combining education, organizational change, policy interventions, and age-inclusive technological design.